Determinant of Implanon Discontinuation among Women Who Ever Used Implanon in Diguna Fango District, Wolayita Zone, Southern Ethiopia: A Community Based Case Control Study - Tadesse, Amanuel; Kondale, Mekides; Agedew, Eskzyiaw; Gebremeskel, Feleke; Boti, Negussie; Oumer, Bilcha (International Journal of Reproductive Medicine, 2017)
Background. A significant number of women make Implanon their first choice of contraception. However, they discontinue their Implanon before its expiry date was high, but factors that contribute to discontinuing their Implanon were poorly described in Ethiopia. Methods. A community based unmatched case control study was conducted. Then simple random sampling technique was used to select 340 women. Data was collected by nurses using face to face interview. Epi-Info version 7 and SPSS 20 software were used. Bivariate and multiple logistic regressions were performed with COR and AOR with 95% CI. Findings. Having preinsertion counseling (AOR: 0.36, 95% CI: 0.20–0.64), having follow-up appointment (AOR: 0.35, 95% CI: 0.2–0.62), age at insertion <20 years (AOR: 3, 95% CI: 1.16–7.8), women who had no formal education (AOR: 2.8, 95% CI: 1.31–6.11), women who had ≤4 children (AOR: 1.8, 95% CI: 1.01–3.21), and women who had previous abortion history (AOR: 2.3, 95% CI: 1.10–4.63) were determinants of Implanon discontinuation. Conclusions. Policy makers and concerned bodies should take into account future intervention and also great emphasis should be given to follow-up appointment and counseling services, especially counseling on side effects, and informed choice for clients after Implanon insertion.